Malaysian Financial Stress Index and Assessing its Impacts on the Economy - Abdullah, Hussin; Dahalan, Jauhari; Hwei, Khaw Lee; Umar, Mohammed; Uddin, Md Mohan (International Journal of Economics and Financial Issues, 2017)
The study further investigates the link between the constructed financial stress index (FSI) and overall economic activity. We approximate the co-movement of the identified financial and economic factors into a single index using the principal component analysis. The combine variables explain about 60% of the total variation in the Malaysian FSI and practically captured the known key aspects of financial stress in Malaysia. The study further applies asymmetric causality and structural vector autoregressive to distinguish between causality in good and bad times and examine the structural impulse responses in changes in the economic activity arising from the shocks in financial stress. The study reveals that changes in the Malaysian FSI (MFSI) negatively affects the economic activity of Malaysia whereas, changes in the economic activity is positively related to the MFSI. Furthermore, the asymmetric causality indicates that high financial stress affect the economic activity during economic recession but economic activity irrespective of whether in boom or recession does not influence the MFSI. However, using the growth rate of foreign trade to proxy economic activity indicates that MFSI influences economic activity irrespective of good or bad times. Nevertheless, economic activity measured using GFD also affect MFSI during the period of economic recession. This also shows that the indicators employed in the construction of the index are the near approximation of the FSI for Malaysia due to its ability to reflect the available information included in the index. The study concludes with policy implications based on the behavior of the MFSI. Keywords: Economic Indicators, Financial Crisis, Malaysian Financial Stress Index JEL Classifications: C43, G01, O47